Respiratory virus shedding in a cohort of on-duty healthcare workers undergoing prospective surveillance - Esbenshade, Jennifer C; Edwards, Kathryn M; Esbenshade, Adam J; Rodriguez, Vanessa E; Talbot, H Keipp; Joseph, Marlon F; Nwosu, Samuel K; Chappell, James D; Gern, James E; Williams, John V; Talbot, Thomas R (Infection control and hospital epidemiology, 2013)
Healthcare-associated transmission of respiratory viruses is a concerning patient safety issue. Surveillance for influenza virus among a cohort of healthcare workers (HCWs) was conducted in a tertiary care children's hospital from November 2009 through April 2010 using biweekly nasal swab specimen collection. If a subject reported respiratory symptoms, an additional specimen was collected. Specimens from ill HCWs and a randomly selected sample from asymptomatic subjects were tested for additional respiratory viruses by multiplex polymerase chain reaction (PCR). A total of 1,404 nasal swab specimens were collected from 170 enrolled subjects. Influenza circulated at very low levels during the surveillance period, and 74.2% of subjects received influenza vaccination. Influenza virus was not detected in any specimen. Multiplex respiratory virus PCR analysis of all 119 specimens from symptomatic subjects and 200 specimens from asymptomatic subjects yielded a total of 42 positive specimens, including 7 (16.7%) in asymptomatic subjects. Viral shedding was associated with report of any symptom (odds ratio [OR], 13.06 [95% confidence interval, 5.45-31.28]; [Formula: see text]) and younger age (OR, 0.96 [95% confidence interval, 0.92-0.99]; [Formula: see text]) when controlled for sex and occupation of physician or nurse. After the surveillance period, 46% of subjects reported working while ill with an influenza-like illness during the previous influenza season. In this cohort, HCWs working while ill was common, as was viral shedding among those with symptoms. Asymptomatic viral shedding was infrequent but did occur. HCWs should refrain from patient care duties while ill, and staffing contingencies should accommodate them.